2009
DOI: 10.1086/597390
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide–Producing Lactobacilli Inhibit Gonococci In Vitro but Not during Experimental Genital Tract Infection

Abstract: H2O2-producing commensal lactobacilli inhibit N. gonorrhoeae in vitro and clinical data suggest they are associated with reduced risk of gonorrhea. Here we pre-colonized mice with Lactobacillus crispatus and then challenged them with N. gonorrhoeae to measure the effects of H2O2-producing lactobacilli on gonococcal infection. We found no difference in the duration of infection or number of gonococci recovered from untreated mice and mice colonized with L. crispatus. A gonococcal catalase mutant and a catalase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 49 publications
1
32
0
1
Order By: Relevance
“…Muench et al . () reported that the murine vaginal pH values were not directly related to the numbers of lactobacilli in the vaginal tract.…”
Section: Discussionmentioning
confidence: 97%
“…Muench et al . () reported that the murine vaginal pH values were not directly related to the numbers of lactobacilli in the vaginal tract.…”
Section: Discussionmentioning
confidence: 97%
“…Some commensal microbes may protect against Gc through competition for nutrients or adherence receptors, and the release of inhibitory factors. Reported associations between vaginal H 2 O 2 -producing lactobacilli and a reduced risk of gonorrhea [106] are countered by co-colonization studies in mice [107] and the demonstration that biofilms protect Gc from these commensals (Apicella, et al, 2012 IPNC abstract #0064). The vaginal microbiota of susceptible and uninfected women exposed to Gc could be comprehensively defined using modern genomic technology.…”
Section: Figmentioning
confidence: 99%
“…While the mechanism by which estradiol promotes long-term colonization in female mice is not known, it is likely that promotion of an estrus-like state is beneficial for the gonococcus based on the fact that untreated mice can be transiently colonized with N. gonorrhoeae provided they are inoculated in the proestrus stage of the reproductive cycle (7,46). The 17␤-estradiol-treated mouse model has been a useful system for studying many aspects of gonococcal infection, including gonococcal evasion of PMN killing (43,49) and antimicrobial peptides (23,48), antigenic variation in vivo (41), and interactions between N. gonorrhoeae and commensal flora (32). This model is based on the use of BALB/c mice.…”
mentioning
confidence: 99%